(Women’s Rights among International Instruments and Algerian Legislation (Comparative Study - Doidi, Aisha (Journal of Economic, Administrative and Legal Sciences, 2017)
Focused on the United Nations since its inception women’s rights without any discrimination between men and women, Vchrist right to education, through resistance to discrimination in education Treaty, and their right to enjoy political rights through three international documents is the Political Rights of Women, the Convention on Elimination of All Forms discrimination against women, on civil and political rights, which asked the Member States to abide by securing equality between spouses in the rights and responsibilities of the marriage, during marriage and at its dissolution and the international Covenant. ILO also focused on women’s work, issued a number of international conventions in this regard, including the Maternity Protection Convention, and the Convention on the prohibition of night work for women, the Convention on equal pay between male and female workers at the equal value of work, and the Convention on discrimination in employment and occupation. On the basis of the principles of equality and equal opportunities between men and women and a commitment to the principles and international resolutions to abolish all forms of discrimination on grounds of sex, it made Algeria efforts to guarantee women’s rights and the equality between men and women in rights and duties, and this was confirmed by the constitutions of the Algerian successive constitutional amendment for the year 2016 and the various legislation the most important of the national Labour and social security and the family Law Act and order No. 76-35 on the organization of education and training modified and complemented.